2015
DOI: 10.1021/acs.est.5b01594
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Matrix PVDF Membranes With in Situ Synthesized PAMAM Dendrimer-Like Particles: A New Class of Sorbents for Cu(II) Recovery from Aqueous Solutions by Ultrafiltration

Abstract: Advances in industrial ecology, desalination, and resource recovery have established that industrial wastewater, seawater, and brines are important and largely untapped sources of critical metals and elements. A Grand Challenge in metal recovery from industrial wastewater is to design and synthesize high capacity, recyclable and robust chelating ligands with tunable metal ion selectivity that can be efficiently processed into low-energy separation materials and modules. In our efforts to develop high capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…In recent decades, copper has becomes one of the popular technology metals in the industrial field. It is widely used from electrical wires to integrated circuits and thin-film solar cells [6], but copper ions show toxicity to humans, living organisms, and the environment [7]. From this point of view, the removal of the heavy metal ions that are poisoning the aqueous environment is an issue which needs a continuous research effort, in addition to the restriction of the use of toxic heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, copper has becomes one of the popular technology metals in the industrial field. It is widely used from electrical wires to integrated circuits and thin-film solar cells [6], but copper ions show toxicity to humans, living organisms, and the environment [7]. From this point of view, the removal of the heavy metal ions that are poisoning the aqueous environment is an issue which needs a continuous research effort, in addition to the restriction of the use of toxic heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…The ATR-FTIR spectra of the PVDF membrane and PVDF/PAMAM-Pal membrane are compared in curves a–e in Figure 5. The characteristic FTIR bands of PVDF membrane still existed for PVDF/PAMAM-Pal membranes, which suggested that the structure of PVDF was not destroyed [40]. In addition, PVDF/PAMAM-Pal membranes had new absorption bands at 1650 cm −1 and 1545 cm −1 due to bending vibrations of N–C=O bonds (amide II) and stretching vibrations of C–N groups [30].…”
Section: Resultsmentioning
confidence: 99%
“…The desorption experiments showed that PVDF-g-PAA-PAMAM membranes had excellent recycling performance. Kotte et al (2015) prepared a novel mixed matrix polyvinylidene fluoride (PVDF) composites membrane via one-pot method, which contained in situ synthesized polyamide-amines (PAMAMs) particles, and investigated its adsorption performance for Cu(II). The present experiment shows that the mixed matrix PVDF membranes can act as a novel high-capacity adsorbent to recover Cu(II) from aqueous solution.…”
Section: Pamams Grafted Organic Polymer Materialsmentioning
confidence: 99%